International Handbook of Practical Theology - Gräb, Wilhelm; Weyel, Birgit; Lartey, Emmanuel; Wepener, Cas (De Gruyter Reference, 2022)
A practical theology, that wants to face the complexity, plurality and differentiation of situations and contexts of religious practices from a global point of view, needs to refer to the discourses that shape them. The contributions can be divided into the sections 'concepts of religion', 'religious practices', and 'discourses', their aim is to identify the respective religious-cultural context and the related framework of interpretation.